Student access to the National University of Equatorial Guinea: prior guidance needs - Nso-Mangue, María Lourdes (2023)
The absence of guidance in the Equatoguinean educational system dates back to the Spanish colony. Today, guidance is recognized as a right of all students. The objective of the research of this article is to diagnose the guidance needs of university students in Equatorial Guinea, prior to their access to the university, and thus, to present the results to the educational authorities in case they believe it is convenient to design proposals for the implementation of guidance services in this student population. A quantitative, non-experimental, exploratory-descriptive approach was used through a survey. The study sample is composed of 404 students of the National University of Equatorial Guinea. The instrument for the collection of information is a questionnaire of university orientation needs of the students elaborated for this purpose. The descriptive results show that there is little information regarding the choice of career, as well as a variety of academic problems and dissatisfaction with current studies. This would mean that this group of students presented needs of academic-professional orientation in the choice of their university career, and academic and personal needs during their studies at the university. The results of this research reveal a concern for attending to the needs and difficulties faced by Equatoguinean students throughout their university education.